MENJELAJAHI KEARIFAN LOKAL PESISIR : MENGEDUKASI KECINTAAN GENERASI MUDA PADA BUDAYA MARITIM - Amir, Amriani (Program Studi Ilmu Kelautan, FMIPA Universitas Tanjungp, 2024)
The coast of Indonesia holds an extraordinary wealth of maritime culture, but today's young generation is starting to forget about local coastal wisdom. Community service activities carried out at SMPN 8 Sungai Kakap, Kubu Raya Regency, aim to foster and strengthen a sense of pride and love for maritime culture among the younger generation. The method used was interviews and counseling involving 20 grade 11 students. The results of the activity show that this activity is effective in increasing students' knowledge and awareness about maritime culture, as well as encouraging their participation in preserving maritime culture and the environment.Keywords:coastal local wisdom, education, maritime culture, young generation, pkm